1997
DOI: 10.1021/la960683p
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Multilamellar Vesicles in the Lamellar Phase of an Electrostatic Lyotropic Ternary System. A Solid State 2H-NMR and Freeze Fracture Electron Microscopy Study

Abstract: Deuterium solid state NMR and freeze fracture electron microscopy experiments have been carried out in the lamellar Lα phase of the water−sodium dodecyl sulfate−octanol system. Within the lamellar phase two types of bilayer organizations have been found. At high surfactant and alcohol concentrations, the lamellar phase is made of a stack of flat parallel bilayers while in the dilute part, it consists of multilayered vesicles of large radius (ca. 10 000 Å). These latter structures, commonly called spherulites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…45 The residual couplings arise from the anisotropy of the rotational motions of the water molecules and thus depend on the curvature of the hydrophobic/hydrophilic interface. 24,43,44,46,47 When D 2 O molecules experience a macroscopically anisotropic environment, the quadrupolar interaction has a nonzero average, leading to a splitting of the resonance. In the case of uniaxial symmetry, as for the L R phase, the 2 H spectrum consists of a doublet with a frequency separation ∆ν given by 45,48 ∆ν )…”
Section: Methodsmentioning
confidence: 99%
“…45 The residual couplings arise from the anisotropy of the rotational motions of the water molecules and thus depend on the curvature of the hydrophobic/hydrophilic interface. 24,43,44,46,47 When D 2 O molecules experience a macroscopically anisotropic environment, the quadrupolar interaction has a nonzero average, leading to a splitting of the resonance. In the case of uniaxial symmetry, as for the L R phase, the 2 H spectrum consists of a doublet with a frequency separation ∆ν given by 45,48 ∆ν )…”
Section: Methodsmentioning
confidence: 99%
“…This could be the situation of large polydispersed (giant) vesicles, especially vesicles with size >5 µm have been detected in the two-phase region of the phase diagram [17]. Auguste et al found a powder pattern characteristic to a spontaneously formed large MLV with radius of 10 µm for a diluted SDS/octanol system [26]. The thermodynamic stability of Lam 1 phase has been observed by following the spectra during 3 months.…”
Section: Deuterium Nmrmentioning
confidence: 99%
“…1 Over the last three decades, 2 H NMR has proven to be a very useful tool for this purpose. [2][3][4][5][6][7][8][9] The measurement of the 2 H quadrupolar couplings provides an insight into the order profiles of C-D bonds and can reveal information about molecular orientation and motion in lipid membranes as well as other liquid crystalline systems.…”
Section: Introductionmentioning
confidence: 99%